I
[tex]3x-4=5x-6\\\\3x-5x=-6+4\\\\-2x=-2\ /\ :\ (-2)\\\\x=1[/tex]
[tex]8x-(5-2x)=3x+2\\\\8x-5+2x=3x+2\\\\10x-3x=2+5\\\\7x=7\ /\ :\ 7\\\\x=1[/tex]
[tex]\frac23(1-x)-1\frac13=\frac13(x-6)+\frac13\\\\\frac23(1-x)-\frac43=\frac13(x-6)+\frac13\ /\ \cdot\ 3\\\\2(1-x)-4=1(x-6)+1\\\\2-2x-4=x-6+1\\\\-2x-x=-5-2+4\\\\-3x=-3\ /\ :\ (-3)\\\\x=1[/tex]
III
[tex]2x-3=\frac13x+2\ /\ \cdot\ 3\\\\6x-9=x+6\\\\6x-x=6+9\\\\5x=15\ /\ :\ 5\\\\x=3[/tex]
[tex]-5x+4=3-2(x+4)\\\\-5x+4=3-2x-8\\\\-5x+2x=-5-4\\\\-3x=-9\ /\ :\ (-3)\\\\x=3[/tex]
[tex]2(4-x)-3=-3(x-4)-4\\\\8-2x-3=-3x+12-4\\\\-2x+3x=8-8+3\\\\x=3[/tex]